2021
DOI: 10.3389/fmicb.2021.748121
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Porphyromonas gingivalis Persisters Through Colloidal Bismuth Subcitrate Synergistically Combined With Metronidazole

Abstract: Microbial persisters enable the development of certain intrinsic strategies for survival with extreme tolerance to multiple antimicrobials. Porphyromonas gingivalis is considered to be the “keystone” periodontopathogen. Indeed, periodontitis, as a highly common inflammatory disease, is the major cause of severe tooth loss and edentulism in adults globally, and yet it is crucially involved in various systemic comorbidities like diabetes. We have recently revealed P. gingivalis persisters-induced perturbation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…More studies are required to develop novel and precise approaches to tackling microbe-induced inflammatory diseases and systemic comorbidities. Indeed, we have recently demonstrated that bismuth drugs can rescue P. gingivalis -perturbed innate host responses [ 50 ], and P. gingivalis persisters could be effectively eliminated via the synergistic combination of bismuth drugs such as colloidal bismuth subcitrate (CBS) with metronidazole [ 51 ]. Further studies are required to develop new anti-persister drug delivery systems to effectively tackle bacterial persisters and modulate dysregulated immunoinflammatory responses to control P. gingivalis -related diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies are required to develop novel and precise approaches to tackling microbe-induced inflammatory diseases and systemic comorbidities. Indeed, we have recently demonstrated that bismuth drugs can rescue P. gingivalis -perturbed innate host responses [ 50 ], and P. gingivalis persisters could be effectively eliminated via the synergistic combination of bismuth drugs such as colloidal bismuth subcitrate (CBS) with metronidazole [ 51 ]. Further studies are required to develop new anti-persister drug delivery systems to effectively tackle bacterial persisters and modulate dysregulated immunoinflammatory responses to control P. gingivalis -related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, P. gingivalis was cultured in broth for 48 h and re-suspended in fresh broth to an OD600 of 0.1. Subsequently, the bacteria were incubated in the stationary phase (72 h) and further treated with metronidazole (MTZ, Sigma-Aldrich, St. Louis, MO, USA) at 100 mg L −1 for 6 h. It was confirmed by our recent study that about 1% of the P. gingivalis cells remained viable after the 6 h MTZ treatment [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…19 The ions present in treatment can inhibit protein/ATP synthesis while disrupting the membrane function. Lately, some studies have shown that bismuth exhibits promising antibacterial and antiviral effects on the keystone periodontopathogen Porphyromonas gingivalis 20,21 and SARS-CoV-2. 22 Besides being a promising candidate for antimicrobial agents, metal ions can also reduce the development of AMR and restore the sensitivity of microbes to the antibiotics when coadministered, 18 suggesting that different chemotherapeutic agents applied in combination could greatly enhance the treatment outcomes.…”
Section: Current Strategies For Controlling Infections and Detecting ...mentioning
confidence: 99%
“…In a biofilm, bacteria communicate and have specific tasks [ 106 ]. There are also persistent cells at rest characterized by extreme antimicrobial tolerance [ 107 ]. Based on testing, it has been shown that persistent cells are not mutations but are phenotypic variants [ 102 ].…”
Section: Porphyromonas Gingivalis ( P Gingivalis ...mentioning
confidence: 99%